2014
DOI: 10.1007/s13187-014-0669-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Enrollment of African Americans into Cancer Genetic Studies

Abstract: The enrollment of ethnically diverse populations in genetic and genomic research is vital to the parity of benefits resulting from research with biological specimens. Herein, we discuss strategies that may effectively improve the recruitment of African Americans into genetics studies. Specifically, we show that engaging physicians, genetic counselors, and community members is essential to enrolling participants into genetic studies. We demonstrate the impact of utilizing African American genetic counselors on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…This finding is not unique to these GS study populations (Foster et al 2004; Newington and Metcalfe 2014), but highlights the importance of developing GS study protocols that take into account participant burden and required commitment. Performing genetic testing on saliva instead of a blood sample, providing incentives for participation, and/or offering online or phone options for recruitment and/or consent have all been cited as ways to increase genetic research enrollment (Close et al 2013; Ewing et al 2015; Huynh et al 2014). These practices may also improve enrollment rates in GS projects, an important consideration for future large scale GS research studies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not unique to these GS study populations (Foster et al 2004; Newington and Metcalfe 2014), but highlights the importance of developing GS study protocols that take into account participant burden and required commitment. Performing genetic testing on saliva instead of a blood sample, providing incentives for participation, and/or offering online or phone options for recruitment and/or consent have all been cited as ways to increase genetic research enrollment (Close et al 2013; Ewing et al 2015; Huynh et al 2014). These practices may also improve enrollment rates in GS projects, an important consideration for future large scale GS research studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that large-scale research on biological samples, also referred to as biospecimens, stored in biobanking facilities will ultimately lead to improvements in disease detection rates and reductions in disease morbidity and mortality among all populations represented (Collins and Varmus 2015). Recent studies have identified factors, such as the option of a narrow consent model and protocol transparency, which were found to favorably influence willingness to engage in biobanking research among African American (Ewing et al 2015;Hagiwara et al 2014). If the scientific community improves efforts for inclusion of underrepresented populations in research, then biospecimen research may be a potential avenue through which we better understand the genetic variation of disease in diverse populations and ultimately ameliorate health disparities observed in minority populations disproportionately impacted by cancer and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified the need to demystify and simplify the informed consent process in order to yield greater participation from diverse populations. 8,[25][26][27] These studies highlight the need to ensure that culturally sensitive and approachable language is used in addition to providing a variety of consent models. Therefore, analysis of informed consent acceptance in diverse populations may be informative in increasing participation from diverse participants in biobank efforts.…”
Section: Introductionmentioning
confidence: 99%